Penyuluhan Kesehatan Tentang Asam Urat Dan Pemberian Rebusan Daun Salam Untuk Mengurangi Kadar Asam Urat Di Desa Kalibuntu Kecamatan Losari Kabupaten Brebes - Ahmad Zakiudin; Vicky Liza Nabila (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2024)
Gouty arthritis is an autoimmune disease that occurs in 0.1-0.5% of the population and three-quarters of them are women. According to several researchers, the trigger factors for gout show that the interaction between environmental and genetic factors plays an important role. Genetic factors that play a role in the occurrence of gout arthritis and the severity of gout arthritis are smoking habits, silica inhalation, bacterial infections, viruses, mycobacteria and the hormone estrogen. The aim of this activity is to understand gout and administer bay leaf decoction to determine the efficacy of bay leaf decoction in gout patients. Health education about gout and boiled bay leaves can increase the knowledge of Kalibuntu Village residents to make all efforts to treat gout using traditional medicine. This outreach to residents can increase residents' knowledge and skills in using traditional medicine in a simple way.